KARAKTERISTIK KADAR AIR DAN SIFAT ORGANOLEPTIK TELUR ITIK ASIN PADA BERBAGAI LAMA PENGASAPAN - Nanda Fatmala; Diah Fridayati; Koji Al Adam (Jurnal Agriovet, 2026)
Egg preservation through the smoking process is carried out by utilizing heat and smoke compounds produced from the combustion of specific materials. This study aimed to evaluate the effect of smoking duration on the moisture content and organoleptic quality of salted duck eggs. The experiment was arranged using a Completely Randomized Design (CRD) with five smoking durations (0, 3, 6, 9, and 12 hours) and four replications. The observed parameters included moisture content, shell color, aroma, and panelists’ preference level. The collected data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT). The results indicated that variations in smoking duration did not significantly affect the moisture content but had a significant effect on the organoleptic quality of salted duck eggs. The smoking process tended to reduce the moisture content, with values ranging from 39.41% to 54.45%. Organoleptic characteristics improved as the smoking duration increased, with the best results obtained in P4 (12 hours of smoking), which achieved scores of 3.95 for shell color, 3.45 for aroma, and 6.55 for overall preference. Therefore, a smoking duration of 12 hours produced the best quality salted duck eggs, characterized by a darker brown shell color, a stronger smoky aroma, and a high level of panelist acceptance. In addition, the moisture content remained within an acceptable range, indicating that the product quality was well maintained. Keywords: Moisture content, organoleptic properties, salted duck eggs,  smoking